ISU ISU STRATEGIS MENUJU PEMBENTUKAN KOMUNITAS EKONOMI ASEAN - Elisabeth, Adriana (Jurnal Penelitian Politik, 2010)
ASEAN Community in 2015 will be achieved through three pillars ASEAN Political Security Community APSC ASEAN Economic Community AEC andASEANSocio Cultural Community ASCC In order to assess the realization ofAEC this research focuses on free trade service and investment Generally intra ASEAN trade and investment is smaller than from extra ASEAN This is one reason to know what ASEAN members have been doing to materialize the AEC in 2015 with thefact that economic growth within ASEAN remains relatively unequal In particular to what extent is the role ofIndonesia in coordinating automotive and other sectors to improve its economy trade and investment The most controversial is how ASEAN can be a single market andproduction base without establishing customs union as well as the European Union did before